Odpowiedź :
Odpowiedź:
4x + 3
4*7 + 3 = 28 + 3 = 31
----------------------------------
5y + 10
5* -4 + 10 = -20 + 10 = -10
----------------------------------
9(7 - a)
9(7 - 0) = 9*7 = 63
---------------------------------
6 - 14b
6 - 14*1/7 = 6 - 2 = 4
---------------------------------
Szczegółowe wyjaśnienie:
Mam nadzieję że pomogłam :)
Odpowiedź:
a) dla x = 7
4x + 3 = 4 · 7 + 3 = 28 + 3 = 31
b) dla y = -4
5y + 10 = 5 · (-4) + 10 = - 20 + 10 = - 10
c) dla a = -0
9(7 - a) = 9(7 - 0) = 9(7) = 63
d) dla b = 1/7
6 - 14b = 6 - 14 · 1/7 = 6 - 14/7 = 4
Szczegółowe wyjaśnienie:
(Mam nadzieję, że pomogłam)